Comparative efficacy and safety and dolutegravir and lamivudine in treatment naive HIV patients. (1st September 2019) - Radford, Matthew; Parks, Daniel C.; Ferrante, Shannon; Punekar, Yogesh
Abstract : Objective: Compare the efficacy and safety of the 2-drug antiretroviral therapy regimen dolutegravir + lamivudine (DTG + 3TC) with traditional 3-drug regimens in treatment-naive patients with HIV-1. Design: Data from double-blind, randomized controlled trials of at least 48 weeks' duration in treatment-naive patients with HIV-1 identified by systematic review were evaluated using a Bayesian network meta-analysis methodology. Methods: The primary outcome was virologic suppression at Week 48 for 3-drug regimens versus DTG + 3TC (also analyzed in patient subgroup with baseline viral load >100 000 RNA copies/ml). Secondary outcomes included CD4 + cell count change from baseline and safety (adverse events, serious adverse events, and drug-related adverse events) at Week 48. Results: The network contains 14 unique regimens from 14 randomized controlled trials based on data from 10 043 patients. The proportional difference for viral suppression at 48 weeks for DTG + 3TC versus the other 13 regimens included in the network ranged from −2.7% (−11.0, 5.6%) versus DTG + tenofovir alafenamide/emtricitabine (FTC) to 7.3% (0.6, 13.8%) versus efavirenz + tenofovir disoproxil fumarate/FTC. DTG + 3TC was found to be significantly better than efavirenz + tenofovir disoproxil fumarate/FTC and similar to all other regimens analysed in terms of viral suppression at 48 weeks. With regard to other outcomes (CD4 +, adverse event, serious adverse event, drug-related adverse events) at 48 weeks, DTG+3TC was broadly similar to all regimens analysed. Conclusion: This network meta-analysis demonstrates similar efficacy and safety outcomes over 48 weeks with DTG + 3TC compared with traditional 3-drug antiretroviral therapy regimens. Abstract : Supplemental Digital Content is available in the text